Caracterização e potencial antioxidante do fruto da palma (Tacinga inamoena) e do mandacaru (Cereus jamacaru) - Lima, Rydley Klapeyron Bezerra (2016)
There are several native and exotic fruit species of economic importance with potential for exploration in semi-arid region. The Tacinga inamoena and Cereus jamacaru are native plants of the Northeast region, which are distributed throughout most of the semi-arid, with great potential among the cacti. The study aimed to characterize the physical, chemical and antioxidant potential of the pulp and peel of fruits of palm and native mandacaru. The experiment was completely randomized, with 4 repetitions. The fruits of Tacinga inamoena and Cereus jamacaru were obtained from populations of plants that are found spontaneous and dispersed in the Caatinga, located in the cities of Angicos and Mossoró-RN. The fruits were harvested directly from the plant and taken to the Laboratory of Physiology and Technology of Fruit Postharvest of the Universidade Federal Rural do Semi-Árido (UFERSA) in Mossoró-RN, at which time it we determined: fresh fruit mass, fruit yield, longitudinal and transverse diameter, firmness, titratable acidity, relation SS/AT, pH, soluble solids, total and reducing sugars, vitamin C, yellow flavonoids, total carotenoids, total anthocyanins, polyphenols total extractable, betalains and antioxidant activity. The pulp of the fruits of Tacinga inamoena have high levels of phosphorus, potassium, calcium, magnesium and titratable acidity; they are also sources of vitamin C. The fruit pulp of Cereus jamacaru has high levels of calcium and potassium, low levels of acidity and high content of sugars and soluble solids/acidity ratio. The peel of fruits of Cereus jamacaru has high levels of calcium, magnesium and phosphorus. The pulp of fruits of Tacinga inamoena and the pulp and peel of the fruit Cereus jamacaru have significant levels of phenolic compounds and betalains; however, it has a low content of anthocyanins, carotenoids, flavonoids and antioxidant activity by ABTS method. With Basis on quality variables evaluated in this study, we say the fruits of Tacinga inamoena and Cereus jamacaru have the potential for commercialization in natura and industrialization